2019
DOI: 10.1177/0748730419828102
|View full text |Cite
|
Sign up to set email alerts
|

Sex Moderates Relationships Among School Night Sleep Duration, Social Jetlag, and Depressive Symptoms in Adolescents

Abstract: Social jetlag, a misalignment between sleep timing on the weekend and work week, is associated with depressive symptoms among adults across both sexes. One prior study found that later sleep timing was associated with depressive symptoms in women but not men. To date, however, no research has investigated whether the association between social jetlag and depression varies by sex among adolescents. The current study assessed self-reported sleep, depressive symptoms, and demographic information from 3,058 adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 77 publications
3
24
4
2
Order By: Relevance
“…Results bolster calls to give sleep the same attention traditionally devoted to PA and screen use. Our findings augment evidence of an inverse association between sleep and depressive symptoms (39,(41)(42)(43)45,52,53) and conflict with studies that found no prospective effect (54,77)or an effect in females only (46,47). Once considered a core symptom or comorbidity of depressive disorders, some now identify sleep problems as both a prodromal manifestation and an independent risk factor for subsequent episodes, predicting the occurrence and outcome of depressive disorders (78).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Results bolster calls to give sleep the same attention traditionally devoted to PA and screen use. Our findings augment evidence of an inverse association between sleep and depressive symptoms (39,(41)(42)(43)45,52,53) and conflict with studies that found no prospective effect (54,77)or an effect in females only (46,47). Once considered a core symptom or comorbidity of depressive disorders, some now identify sleep problems as both a prodromal manifestation and an independent risk factor for subsequent episodes, predicting the occurrence and outcome of depressive disorders (78).…”
Section: Discussioncontrasting
confidence: 64%
“…However, while cross-sectional associations between short sleep and depressive symptoms are well established (39,(41)(42)(43)(44); a paucity of longitudinal population-level research exists and available prospective evidence is inconsistent. Some results suggest a bidirectional relationship or reverse causality (29,31,45), and others signify sex and gender differences; often with inverse associations between sleep duration and depressive symptoms in females only, and weaker or null effects in males (46,47).…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate binary logistic regression was used to analyze the adjusted OR between the dependent and independent variables, thus controlling for the possible effect modifiers and potential confounders in the binary logistic regression models. Different kinds of electronic use and social jetlag have been shown to be significantly affected by socio-economic status, age, and sex in earlier studies Short and Louca, 2015;Komada et al, 2019;Mathew et al, 2019). Therefore, in this study, these three factors were adjusted in the multivariate binary logistic regression analysis model.…”
Section: Discussionmentioning
confidence: 99%
“…In studies among adolescents, social jetlag has been found to be associated with an unhealthy dietary pattern, depressive symptoms, and multiple metabolic risks (Levandovski et al, 2011;Wong et al, 2015;Koopman et al, 2017;Almoosawi et al, 2018;Mota et al, 2019). Surprisingly, female participants with social jetlag had more depressive symptoms compared to men (Mathew et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…Some results suggest a bi-directional relationship or reverse causality (29,31,43), and others signify sex and gender differences; often with inverse associations between sleep duration and depressive symptoms in females only, and weaker or null effects in males (44,45).…”
Section: Introductionmentioning
confidence: 99%